2021
DOI: 10.1029/2020jc017140
|View full text |Cite
|
Sign up to set email alerts
|

Bias Correction of Ocean Bottom Temperature and Salinity Simulations From a Regional Circulation Model Using Regression Kriging

Abstract: Climate and circulation model simulations estimate climatological and environmental variables continuously across space from the past to present and sometimes into the future. The continuous nature of these estimates provides valuable information that is essential for assessing the impacts of climatological and environmental changes. However, it is well known that these simulation outputs are often systematically biased relative to observations at spatial and temporal scales of interest, and require bias corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We then showed that DSEM can be specified using 'arrow-andlag' notation, which is parsed to construct the sparse precision matrix for a GMRF, and this in turn is fitted within a GLMM. We first debates continue regarding the performance of these methods (Chang et al, 2021;Yang et al, 2018). Similarly, nonparametric and nonlinear interactions have been estimated using artificial neural networks to approximate nonlinear differential equations (Bhat & Munch, 2022;Bonnaffé & Coulson, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then showed that DSEM can be specified using 'arrow-andlag' notation, which is parsed to construct the sparse precision matrix for a GMRF, and this in turn is fitted within a GLMM. We first debates continue regarding the performance of these methods (Chang et al, 2021;Yang et al, 2018). Similarly, nonparametric and nonlinear interactions have been estimated using artificial neural networks to approximate nonlinear differential equations (Bhat & Munch, 2022;Bonnaffé & Coulson, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Methods are increasingly available to estimate nonlinear causality among multiple variables in ecological systems. For example, convergent cross‐mapping has been used to predict system properties in experimental settings (Deyle et al., 2016), although debates continue regarding the performance of these methods (Chang et al., 2021; Yang et al., 2018). Similarly, nonparametric and nonlinear interactions have been estimated using artificial neural networks to approximate nonlinear differential equations (Bhat & Munch, 2022; Bonnaffé & Coulson, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The use of interpolation and fitting techniques for simulating atmospheric pollutant concentrations has been a consistent focus of research. The accuracy and precision of interpolation have always been key considerations in these studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In the study by Li et al [31], the results indicated that the optimal polynomial fitting (OPF) method accurately reconstructed PM 2.5 fields.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial interpolation methods, widely employed in atmospheric studies and other fields, offer a solution by mitigating the impact of insufficient ground-based observation data on accurately characterizing the spatial and temporal distribution characteristics of PM 2.5. These methods include spatiotemporal statistical models based on Kriging interpolation, spatial and temporal regression models based on Kriging interpolation integrated with remote-sensing AOD data, neural network models based on RBF interpolation, and 3D RBF interpolation for hydrological structure analysis [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the spatial estimation of ocean information, studies providing gridded data such as OISST (Optimum Interpolation SST [Sea Surface Temperature]) are ongoing 22 24 . In addition, research is being conducted to remove the bias of numerical models using spatial estimation techniques such as Kriging 25 . However, these techniques mainly focus on temperature and salinity.…”
Section: Background and Summarymentioning
confidence: 99%